2022
DOI: 10.3389/fneur.2022.967946
|View full text |Cite
|
Sign up to set email alerts
|

Impact of epilepsy and its treatment on brain metastasis from solid tumors: A retrospective study

Abstract: IntroductionRetrospective observational study on medical records of patients with epilepsy related brain metastases (BM) to evaluate efficacy, safety and possible interaction with cancer treatment of different anti-seizure medications (ASMs) and the risk of seizures.Materials and methodsWe consecutively reviewed all medical records of epilepsy-related BM patients from 2010 to 2020 who were followed for at least one month at the Brain Tumour-related Epilepsy Center of the IRCCS Regina Elena National Cancer Inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Some demographic aspects have been scarcely analyzed in previous studies, and there is no clear consensus on the results obtained. Thus, while Puri et al (2020) [36] et al reported that age is the only variable that correlates negatively with the occurrence of pre-and postoperative seizures, other authors such as Witteler et al (2020) [37] and Maschio et al (2022) [38] did not observe any significant correlation between age and seizure risk. In our study, no statistically significant differences were found with respect to either sex (p = 0.061) or age (p = 0.753).…”
Section: Discussionmentioning
confidence: 92%
“…Some demographic aspects have been scarcely analyzed in previous studies, and there is no clear consensus on the results obtained. Thus, while Puri et al (2020) [36] et al reported that age is the only variable that correlates negatively with the occurrence of pre-and postoperative seizures, other authors such as Witteler et al (2020) [37] and Maschio et al (2022) [38] did not observe any significant correlation between age and seizure risk. In our study, no statistically significant differences were found with respect to either sex (p = 0.061) or age (p = 0.753).…”
Section: Discussionmentioning
confidence: 92%